الإعلام الجديد، ضوابطه وأخلاقياته ومساهمته في الدعوة الإسلامية - عتير، الطيب (University Of Eloued جامعة الوادي, 2025)
تبحث هذه الأطروحة، المعنونة ب "الإعلام الجديد ضوابطه، أخلاقياته، ومساهمته في الدعوة الإسلامية"، مدى مساهمة الإعلام الجديد في الدعوة الإسلامية ضمن إطار المبادئ الأخلاقية والقانونية الوضعية والشرعية المعمول بها. ويتمحور السؤال البحثي الرئيسي الذي يوجه هذه الدراسة حول: إلى أي مدى يمكن للإعلام الجديد أن يكون وسيلة فعالة للدعوة، مع الحفاظ على اتساقه مع كل من التشريعات الوضعية والمعايير الأخلاقية الإسلامية؟ وللإجابة على هذا السؤال، تتبنى الدراسة منهجا وصفيا تحليليا، يجمع بين التقنيات النوعية والكمية إلى جانب التحليل الاحصائي البسيط. وقد شمل جمع البيانات التحليل المنهجي للمواقع الإلكترونية الإسلامية العامة والخاصة على حد سواء بالإضافة إلى منصات التواصل الاجتماعي الرئيسية مثل فيسبوك ويوتيوب كما تعرف الرسالة الإعلام الجديد بأنه نتاج تكامل التكنولوجيا الحديثة مع الإعلام التقليدي، وتسلط الضوء على خصائصه الرئيسية مثل التفاعلية الكاملة وسرعة النشر. كما تؤكد على أهمية الضوابط والأخلاقيات في ممارسة الإعلام، وتوضح كيف تسهم التشريعات الجزائرية في تنظيم هذا القطاع. تبرز الرسالة كذلك دور الإعلام الجديد كأداة رئيسية للدعوة الإسلامية، مع التركيز على أهمية الدعوة الإسلامية الرقمية"، وتقدم مجموعة من التوصيات لتعزيز هذا الدور، مثل تطوير البنية التحتية وتدريب الدعاة على المهارات الرقمية. تدرس الأطروحة الإعلام الجديد وتأثيره في الدعوة الإسلامية، منظمة في ثلاثة فصول رئيسية بعد الفصل التمهيدي يحدد الفصل الأول المفاهيم والأسس التكنولوجية للإعلام الجديد، ويناقش الفصل الثاني الضوابط والأخلاقيات اللازمة الشرعية والقانونية) الضبط محتواه. ركز الفصل الثالث على الجانب التطبيقي، محللا دور الإعلام الجديد في دعم العمل الدعوي الإسلامي بناءً على الإحصائيات وخلصت الدراسة إلى أن الإعلام الجديد أصبح سلطة خامسة وأداة فعالة للدعوة، رغم تحديات الأخبار الكاذبة وغياب التشريعات الواضحة من النتائج المتوصل إليها بعد الدراسة وتجميع التوصيات هي : ضرورة أن تلحق الدول الإسلامية والعربية بالركب العالمي في التكنولوجيا والإعلام الجديد، وأن يضاعف القائمون على الاتصال الإسلامي جهودهم لاستخدام هذه المنصات، خاصة مواقع التواصل الاجتماعي، في نشر الدعوة الإسلامية للوصول لجميع شرائح المجتمع ويجب على الدعاة مراعاة التدرج في الخطاب وإتقان اللغات الأجنبية، وتوخي الحذر من الانزلاق في المسائل السياسية. ويدعو الملخص القائمين بالحكم والمحسنين إلى دعم وتمويل مراكز توجيه وتكوين الدعاة في مجال الإعلام الجديد، وإلى العمل على تطوير إعلام نظيف وتطبيقات اتصال إسلامية بديلة لحماية المسلمين من المحتوى الضار. تختتم الأطروحة بتلخيص النتائج الرئيسية وتقديم إجابات واضحة لإشكالية البحث المركزية والأسئلة الموجهة، وتؤكد على أنه بينما يتيح الإعلام الجديد فرصا غير مسبوقة للدعوة الإسلامية، يجب أن يظل استخدامه راسخا في كل من المسؤولية الأخلاقية والالتزام بمبادئ الشريعة. Abstract This thesis, titled **"New Media: Its Controls, Ethics, and Contribution to Islamic Da'waa (Preaching)"**, investigates the extent to which new media contributes to Islamic da'waa within the framework of applicable ethical, statutory, and Sharia-based legal principles. The main research question guiding this study is: To what extent can new media be an effective tool for da'waa while maintaining its consistency with both statutory legislation and Islamic ethical standards? To answer this question, the study adopts a **descriptive-analytical methodology**, combining qualitative and quantitative techniques alongside basic statistical analysis. Data collection involved the systematic analysis of Islamic websites—both general and private—in addition to major social media platforms such as Facebook and YouTube. The thesis defines new media as the product of the integration of modern technology with traditional media and highlights its main features, such as **full interactivity and speed of dissemination**. It stresses the importance of **controls and ethics** in media practice and clarifies how Algerian legislation contributes to regulating this sector. Furthermore, the thesis highlights the role of new media as a key tool for Islamic da'waa, focusing on the importance of **"digital Islamic da'waa,"** and offers a set of recommendations to enhance this role, such as improving infrastructure and training preachers in digital skills. The dissertation examines new media and its impact on Islamic da'waa, structured into three main chapters following an introductory chapter. The first chapter defines the concepts and technological foundations of new media, and the second chapter discusses the necessary **controls and ethics** (Sharia and legal) required to regulate its content. The third chapter focused on the applied aspect, analyzing the role of new media in supporting Islamic da'waa work based on statistics. The study concluded that new media has become a fifth estate and an effective tool for da'waa, despite the challenges of fake news and the absence of clear legislation. Among the conclusions reached and recommendations compiled after the study are: the necessity for Islamic and Arab countries to **catch up with the global pace** in technology and new media, and for those involved in Islamic communication to **double their efforts** to use these platforms, especially social media, for disseminating the Islamic message to all segments of society. Preachers must observe **gradualism in discourse**, **master foreign languages**, and exercise caution to avoid being drawn into political issues. The abstract calls upon **rulers and benefactors** to support and fund guidance and training centers for preachers in the field of new media, and to work on developing **clean media** and alternative Islamic communication applications to protect Muslims from harmful content. The thesis concludes by summarizing the key findings and providing clear answers to the central research problem and guiding questions. It affirms that while new media offers unprecedented opportunities for Islamic da'waa, its use must remain firmly rooted in both **ethical responsibility and adherence to Sharia principles.
Thesis
Keywords: الإعلام الجديد; أخلاقيات; الدعوة الإسلامية; New Media; Ethics; Islamic Da'waa